Patient Experiences and Prerequisites of Collaboration as Partners in Person‐Centred Care: An Interview Study - Lena Rosenlund; Sofie Jakobsson; Helen Lloyd; Anna Diffner; Åsa Lundgren‐Nilsson; Anna Dencker (Nursing Open)
ABSTRACT Aim To explore what characterises communication and collaboration within a patient and professional partnership in outpatient care settings garnered from the experiences of persons living with long‐term conditions. Design A qualitative descriptive study design. Methods Semi‐structured individual interviews were conducted with 15 persons with long‐term condition/s who experienced outpatient treatment or follow‐up care. Data were explored through inductive thematic analysis. The COREQ checklist was followed. Results The analysis revealed five themes: adapting and self‐managing in daily life, handling and carrying information, building trust and continuity, acting in a flexible and transparent dialogue and sharing the way forward. The participants described their personal and informal resources, and their actions to take control and manage health and well‐being. A person‐centred approach, sharing of knowledge and communication skills enabled the development of trust in the healthcare providers and their treatment and care. Communication was facilitated through availability, shared documentation, continuity and coordination of care. Collaboration was described as a flexible dialogue with mutual trust and transparency, shared learning and problem‐solving. Sharing the way forward was a process, alongside and important to the life‐changing process to cope with the illness. Conclusions Prerequisites for the collaboration in outpatient settings were availability, continuity and a healthcare system that acknowledged, empowered and adapted to patients' health status, resources, everyday life and a patient's coping processes to manage their disease. For a co‐created, person‐centred outpatient care, it is important to acknowledge and/or collaborate with the patient's team of other healthcare providers and informal caregivers. Relevance to Clinical Practice The study contributes to better understanding of patient preferences and prerequisites how to work in partnership and how to develop future services and person‐centred care for persons living with long‐term conditions. Patient and Public Contribution Patients included in this study were participants during the data collection process.